School Differences in Social–Emotional Learning Gains: Findings From the First Large-Scale Panel Survey of Students. (October 2019) - Loeb, Susanna; Christian, Michael S.; Hough, Heather; Meyer, Robert H.; Rice, Andrew B.; West, Martin R.
Measures of school-level growth in student outcomes are common tools for assessing the impacts of schools. The vast majority of these measures use standardized tests as the outcome of interest, even though emerging evidence demonstrates the importance of social–emotional learning (SEL). In this article, we present results from using the first large-scale panel surveys of students on SEL to produce school-level value-added measures by grade for growth mind-set, self-efficacy, self-management, and social awareness. We found substantive differences across schools in SEL growth, with magnitudes of differences similar to those for growth in academic achievement. In contrast, we found that the goodness of fit of the value-added model was considerably lower when the outcome variables were measures of SEL constructs rather than of academic achievement. In addition, the across-school variance in the average level of the SEL measures was proportionally much smaller than that for academic measures. These findings recommend caution in interpreting measures as the causal impacts of schools on SEL, though they also do not rule out important school effects.